2011
DOI: 10.1515/jpem.2011.115
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of Hashimoto thyroiditis in children and the relationship between urinary iodine level and Hashimoto thyroiditis

Abstract: The aim of this study was to determine the frequency of thyroid autoimmunity in second grade primary school students and to examine the relationship between iodine and Hashimoto thyroiditis (HT). This was a cohort study performed with 1000 students. Urinary iodine levels, antithyroid peroxidase (anti-TPO) and antithyroglobulin (anti-Tg) antibodies were determined in all children. Children with anti-TPO or anti-Tg antibody positivity or with goiter were summoned for detailed examinations. In total, 36 cases (3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…In this study, children with goiter and without thyroiditis presented a median iodine urinary concentration of 73 lg/L, whereas in the group of normal children, the concentration was 81 lg/L. This observation suggests an association between increased iodine ingestion and thyroiditis (17).…”
Section: Introductionmentioning
confidence: 42%
“…In this study, children with goiter and without thyroiditis presented a median iodine urinary concentration of 73 lg/L, whereas in the group of normal children, the concentration was 81 lg/L. This observation suggests an association between increased iodine ingestion and thyroiditis (17).…”
Section: Introductionmentioning
confidence: 42%
“…In our study, antithyroid autoantibodies were found positive in 36.8% of 103 pediatric ITP patients. Considering that the prevalence of antithyroid antibodies in healthy children and adolescents is estimated to be between 3.56% and 5.4% [15], 36.8% positivity detected in the patients with ITP is a remarkable figure.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed that is possibly what we see. As the level of intrathyroidal iodine increases, so does the incident of Hashimoto’s thyroiditis [4], one of the most common autoimmune diseases. However, not everyone develops Hashimoto’s thyroiditis with higher iodine, just some people.…”
Section: To the Editormentioning
confidence: 99%